MNGI-14. LOSS OF HISTONE H3K27me3 IDENTIFIES A SUBSET OF MENINGIOMAS WITH INCREASED RISK OF RECURRENCE. (5th November 2018) - Katz, Leah M; Hielscher, Thomas; Liechty, Benjamin; Silverman, Joshua; Zagzag, David; Sen, Rajeev; Wu, Peter; Golfinos, John; Reuss, David; Neidert, Marian; Wirsching, Hans-Georg; Baumgarten, Peter; et al.
Abstract: Epigenetic patterns on the level of DNA methylation have already shown to separate clinically relevant subgroups of meningiomas. Based on a reference set (Sahm et al., Lancet Oncol 2017), an epigenetic meningioma classifier employing DNA methylation patterns is made available through molecularneurpathology.org. We now set out to identify prognostic implications of epigenetic modification on the proteome level, particularly modifications of histones. First focus was on H3K27 trimethylation (H3K27me3). H3K27me3 was assessed by immunohistochemistry on 232 meningiomas. In 194 cases, trimethylation was detected in tumor cells. In 25 cases, staining was limited to vessels while all tumor cells were negative. Finally, 13 cases yielded equivocal staining patterns. Reduced abundance of H3K27me3 in cases with staining limited to vessels was confirmed by mass spectrometry on a subset of cases. Lack of staining for H3K27me3 in all tumor cells was significantly associated with more rapid progression (p=0.009). In line, H3K27me3 negative cases were associated with a DNA methylation pattern of the more aggressive types among the recently introduced DNA methylation groups. Also, NF2 and SUFU mutations were enriched among cases with lack of H3K27me3 in tumor cells (p<0.0001 and p=0.029, respectively). H3K27me3 staining pattern added significant prognostic insight in WHO grade II cases and in the compound subset of WHO grade I and II cases (p=0.04 and p=0.007, respectively). However, it did not further stratify within WHO grade III cases. Collectively, this data indicate that epigenetic modifications beyond DNA methylation are involved in the aggressiveness of meningioma. It also suggests that H3K27me3 immunohistochemistry might be a useful adjunct in meningioma diagnostics, particularly for cases with WHO grade II histology or at the borderline between WHO grade I and II. Ongoing studies evaluate the role of histone marks other than H3K27me3 and consequences on the proteomic composition of meningioma cells by high-throughput mass spectrometry.